Law Enforcement's Role in Tackling Illegal Gold Mining for Sustainable Development Goals - Puji Prayitno Kuat; Pandu Ramadhan Galih; Nuha Ilmawan Faiz (E3S Web of Conferences)
Illegal gold mining is a significant environmental crime, particularly in resource-rich regions like the Amazon, West Africa, and Southeast Asia. This study uses a qualitative research design to evaluate law enforcement efforts in Brazil, Ghana, and Indonesia. Primary data were collected through semi-structured interviews involving law enforcement personnel, government officials, environmental experts, and local community members affected by mining activities. These interviews aimed to uncover challenges in enforcing environmental laws, the effectiveness of ongoing measures, and local perceptions of enforcement outcomes. Secondary data comprised an extensive academic literature review, official reports, and legal documents to contextualize the findings within global trends. Case studies were selected based on criteria such as the prevalence of illegal gold mining, environmental impacts, and variations in enforcement strategies. Thematic analysis was employed to identify recurring issues such as corruption, resource constraints, and lack of political will. Results indicate that enforcement has had limited success in curbing deforestation, mercury contamination, and biodiversity loss, mainly due to institutional weaknesses. Enforcement measures disproportionately target small-scale miners while larger organized networks evade prosecution. This paper emphasizes the importance of addressing socioeconomic drivers through alternative livelihoods, international collaboration, and enhanced institutional capacity to achieve sustainable development goals.